Leadership for change Developing transformational student leaders through global learning spaces - Wahl, WP (AOSIS, 2020)
This edited volume reveals how the journey of transformation at the University of the Free State (UFS) became interwoven with student leadership development and global learning. The UFS initiated two intersecting co-curricular programmes, namely, the First-Year Leadership for Change (F1L4C) programme in 2010; and the triennial Global Leadership Summit (GLS) in 2012. Although these programmes changed over time, their core focus remained to be the development of transformational student leaders through the creation of global learning spaces. From its inception in 2010 to the last GLS in 2018, the UFS global learning project involved 780 students and 259 staff members from 109 institutions, across four continents. The goal of this edited volume is to create a deeper understanding of how the UFS F1L4C and GLS programmes enhanced student leadership development through global learning, especially in the context of higher education transformation.